Analysis of the Film 5 Eagles as a Character Education Media with the Theme of Social Relations in the School Environment in P5 Activities for Class 4B Students of MI Ma'rif Budiluhur Kertek Wonosobo - Umul Hasanah, Dwi; Haryanto, Sri; Saefullah, Muhammad (DAS Institute, 2024)
This thesis aims: 1) to find out what character education values ​​and social values ​​are contained in the film 5 Eagle; 2) to determine the relevance of character education values ​​in the film 5 Eagle as a medium for character education in P5 activities at MI Ma'arif Budiluhur. This thesis uses a qualitative research approach with the type of research being descriptive. The data collection techniques used in this research are observation, interviews and documentation techniques. The subjects in this research consisted of class 4B students at MI Ma'arif Budlihur Kertek Wonosobo, the homeroom teacher of class 5b, and the principal of MI Ma'arif Budiluhur. Then, data sources were obtained from primary and secondary data sources. In qualitative research, there are several analysis steps, namely data collection, data reduction, data presentation, and conclusions. The results of the research show that: 1) The character values ​​and social values ​​contained in the film 5 Elang as a medium for character education with the theme of social relations in the school environment in P5 activities include a. Honesty, b. Tolerance, c. Social Care d. Discipline e. National spirit f. Caring for the environment g. Creative h. Polite i. Responsibility k. Democratic l. Hard work m. Smart n. Collaboration o. Sincere p. Love peace q. Brave r. Appreciate s' achievements. Friendship t. Empathy u. Justice v. Communication. 2) The relevance of the character values ​​in the film 5 Elang which contribute solidly to character education in P5 activities for class 4B Mi Ma'arif Budiluhur students, namely that there are several values ​​that are relevant and applied in schools, including: the value of cooperation, the value of social care, the value of friendship, responsibility, patience, courage, and mutual help, where these values ​​are the values ​​of character education in the film 5 Elang